Obstetric and neonatal outcomes in pregnant women with left-sided valvular stenosis in a tertiary medical center in Taiwan - Hui-Ling Lee; Hao-Tien Liu; Chi-Yuan Chiang; Shih-Chun Chou; Chung-Chuan Chou (Taiwanese Journal of Obstetrics & Gynecology, 2025)
Objective: Left-sided valvular stenosis increases pregnancy-associated risks. We aim to compare maternal and neonatal outcomes between women with left-sided valvular stenosis and controls and to determine the predictors of adverse pregnancy outcomes. Materials and methods: We retrospectively retrieved data in the Chang Gung Research Database from women who had at least one prenatal examination record or pregnancy-related diagnosis code and gave birth, terminated the pregnancy, or took abortion pills in the hospital and had confirmed aortic stenosis or mitral stenosis based on echocardiographic reports, surgical reports, and discharge summaries. Propensity score matching (PSM) was used to balance covariates between the left-sided valvular stenosis and control groups. Results: Patients in the left-sided valvular stenosis group were of shorter height, lower weight and body mass index, and had a higher rate of atrial fibrillation compared to controls. After PSM, the left-sided valvular stenosis group (n = 52) had more heart failure, chronic kidney disease, and use of digoxin and anticoagulants than did the control group (n = 260). Pregnancy outcomes in the left-sided valvular stenosis group included a higher cesarean section rate, lower gestational age, and a higher rate of newborn intensive care unit transfer than controls. The composite adverse maternal event rate did not differ significantly between the two groups, but the composite adverse neonatal event rate (premature birth, low birth weight) was higher in the left-sided valvular stenosis group. Regional anesthesia was most commonly used during cesarean section in both groups. Left-sided valvular stenosis, heart failure, general anesthesia, and cesarean section were significant factors associated with increased risks of composite adverse neonatal events. Conclusions: Among pregnant women, those with left-sided valvular stenosis had more comorbidities and medication use during pregnancy and were more likely to give birth to premature babies with low birth weight and poor vitality.